Assessment of the Contribution of Local and Regional Biomass Burning on PM2.5 in New York/New Jersey Metropolitan Area - Subraham Singh; Glen Johnson; David W. DuBois; Ilias G. Kavouras (Aerosol and Air Quality Research)
Abstract The sources of fine particulate matter (PM2.5, particles with diameter < 2.5 µm) in four monitoring sites in the New York/New Jersey metropolitan statistical area from 2007 to 2017 were apportioned by positive matrix factorization (PMF) of chemical speciation data. Biomass burning, secondary inorganic (i.e., ammonium sulfate and nitrate) and primary traffic exhausts were the predominant PM2.5 sources. The declining trends of PM2.5 mass in all four sites were very well correlated with decreasing secondary sulfate levels due to SO2 emission reductions by coal-fired power plants. The contributions of secondary nitrate, primary traffic exhausts and diesel particles did not change (or slightly increased) over time except for the Queens site, where statistically significant declines were computed. Biomass burning contributions increased in the Queens and Chester sites but declined in the Division Str and Elizabeth Lab sites, although significant interannual variability was observed. Wintertime biomass burning aerosols were most likely due to combustion of contemporary biomass for industrial and domestic heating, and it was linked to the intensity (average minimum temperature) and duration (number of freezing days) of cold weather. The annual summertime biomass burning contributions were correlated with the number of and area burnt by lightning-ignited wildfires. These results indicate that PM2.5 sources in urban environments is changing from anthropogenic secondary sulfate and nitrate to carbonaceous aerosol from local anthropogenic and regional climate-driven biomass burning. This trend may counterbalance emissions controls on anthropogenic activities and modify the biological and toxicological responses and resultant health effects.